Incorporação do ideário da Garden-City inglesa na urbanística moderna brasileira: Águas de São Pedro - Trevisan, Ricardo (Universidade Federal de São Carlos, 2003)
This work, entitled Inclusion of anthology of ideas from the english Garden-City into Modern Brazilian urban design: Águas de São Pedro developed in the Graduate Course in Urban Engineering at the Federal University of São Carlos (UFSCar), presents a study of the urban plan of Águas de São Pedro town, state of São Paulo, and its relation to the Garden-City s concepts, structured in four different parts. In its first part is given a brief overview of the history of post-Industrial Revolution urbanism, identifying the main urban typologies originating during this time and focusing especially on the Garden City typology from its English origin to its worldwide diffusion. From here, the study delves in the appropriation of this typology by brazilian designers (architects and engineers), articulated with economic, political, social and cultural analysis of this country in the first decades of the XXth Century. The third part analyses the universe of professional responsible for the creation of the city plan of Águas de São Pedro, urban engineer Jorge de Macedo Vieira, identifying his main influences and his productive evolution. Also, others professionals involved with this project are included. Finally, in the fourth part is done a comprehensive study of the adopted plan for the Watering town, along with its due empirical analysis, electing, from there, the elements that relate it to the Garden-City typology. This research therefore adds itself to others that study the use of the Garden-City urban typology in Brazil, contributing in this manner to extend knowledge about a school that participated actively in the history of brazilian urbanism.
Keywords: Renovação urbana; Espaço urbano - história; Modelos urbanos; Planejamento urbano; Urban history; Garden-City movement; New towns; Águas de São Pedro Watering town; Urban planning; Urban project; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO